FAKTOR-FAKTOR UNTUK PENINGKATAN KEMANDIRIAN PETANI DALAM PENGELOLAAN HUTAN RAKYAT: STUDI KASUS DI DESA RANGGANG, KABUPATEN TANAH LAUT, KALIMANTAN SELATAN - Idin Saepudin Ruhimat (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2014)
Lack of farmers' self-reliance is one of inhibiting factors of community forest management in Ranggang village. This study aims to analyze the influencing factors to farmers' self-reliance and to formulate possible improvement efforts. This research was conducted in Ranggang village, using survey method with explanatory approach. The analytical method used is Structural Equation Modeling (SEM) analysis with SmartPLs 2.0 M3 program. Results showed that the farmers ability and dynamic level directly affect to farmers' selfreliance, while socio-cultural environment, farmers characteristics, external support, extention performance, and innovation availability are all have indirect effects. This study concluded that the farmers' self-reliance in community forest management in Ranggang village is low due to lack of farmers ability and dynamism in community forest management Therefore, improvement can be done by increasing farmers ability and dynamism. National and regional governments are advised to strengthen the institutions of education, training and forestry extension, increased capacity of forestry extension workers and availability of technological innovation covering both technical and nontechnical.